Hydrogen-Cycling during Solventogenesis in Clostridium acetobutylicum American Type Culture Collection (ATCC) 824 Requires the [NiFe]-Hydrogenase for Energy Conservation - Katherine L. Germane; Sanchao Liu; Elliot S. Gerlach; Alice M. Savage; Rebecca L. Renberg; Theresah N. K. Zu; Hong Dong; Scott D. Walck; Matthew D. Servinsky; Christian J. Sund (Fermentation, 2018)
Clostridium acetobutylicum has traditionally been used for production of acetone, butanol, and ethanol (ABE). Butanol is a commodity chemical due in part to its suitability as a biofuel; however, the current yield of this product from biological systems is not economically feasible as an alternative fuel source. Understanding solvent phase physiology, solvent tolerance, and their genetic underpinning is key for future strain optimization of the bacterium. This study shows the importance of a [NiFe]-hydrogenase in solvent phase physiology. C. acetobutylicum genes ca_c0810 and ca_c0811, annotated as a HypF and HypD maturation factor, were found to be required for [NiFe]-hydrogenase activity. They were shown to be part of a polycistronic operon with other hyp genes. Hydrogenase activity assays of the ΔhypF/hypD mutant showed an almost complete inactivation of the [NiFe]-hydrogenase. Metabolic studies comparing ΔhypF/hypD and wild type (WT) strains in planktonic and sessile conditions indicated the hydrogenase was important for solvent phase metabolism. For the mutant, reabsorption of acetate and butyrate was inhibited during solventogenesis in planktonic cultures, and less ABE was produced. During sessile growth, the ΔhypF/hypD mutant had higher initial acetone: butanol ratios, which is consistent with the inability to obtain reduced cofactors via H2 uptake. In sessile conditions, the ΔhypF/hypD mutant was inhibited in early solventogenesis, but it appeared to remodel its metabolism and produced mainly butanol in late solventogenesis without the uptake of acids. Energy filtered transmission electron microscopy (EFTEM) mapped Pd(II) reduction via [NiFe]-hydrogenase induced H2 oxidation at the extracelluar side of the membrane on WT cells. A decrease of Pd(0) deposits on ΔhypF/hypD comparatively to WT indicates that the [NiFe]-hydrogenase contributed to the Pd(II) reduction. Calculations of reaction potentials during acidogenesis and solventogenesis predict the [NiFe]-hydrogenase can couple NAD+ reduction with membrane transport of electrons. Extracellular oxidation of H2 combined with the potential for electron transport across the membrane indicate that the [NiFe}-hydrogenase contributes to proton motive force maintenance via hydrogen cycling.